Knots Untie: Molecular Determinants Involved in Knot Formation Induced by Pseudomonas savastanoi in Woody Hosts - Caballo-Ponce, Eloy; Murillo, Jesús; Martínez-Gil, Marta; Moreno-Pérez, Alba; Pintado, Adrián; Ramos, Cayo (Frontiers in Plant Science, 2017)
The study of the molecular basis of tree diseases is lately receiving a renewed attention, especially with the emerging perception that pathogens require specific pathogenicity and virulence factors to successfully colonize woody hosts. Pathosystems involving woody plants are notoriously difficult to study, although the use of model bacterial strains together with genetically homogeneous micropropagated plant material is providing a significant impetus to our understanding of the molecular determinants leading to disease. The gammaproteobacterium Pseudomonas savastanoi belongs to the intensively studied Pseudomonas syringae complex, and includes three pathogenic lineages causing tumorous overgrowths (knots) in diverse economically relevant trees and shrubs. As it occurs with many other bacteria, pathogenicity of P. savastanoi is dependent on a type III secretion system, which is accompanied by a core set of at least 20 effector genes shared among strains isolated from olive, oleander and ash. The induction of knots of wild-type size requires that the pathogen maintains adequate levels of diverse metabolites, including the phytohormones indole-3-acetic acid and cytokinins, as well as cyclic-di-GMP, some of which can also regulate the expression of other pathogenicity and virulence genes and participate in bacterial competitiveness. In a remarkable example of social networking, quorum sensing molecules allow for the communication among P. savastanoi and other members of the knot microbiome, while at the same time are essential for tumor formation. Additionally, a distinguishing feature of bacteria from the P. syringae complex isolated from woody organs is the possession of a 15 kb genomic island (WHOP) carrying four operons and three other genes involved in degradation of phenolic compounds. Two of these operons mediate the catabolism of anthranilate and catechol and, together with another operon, are required for the induction of full-size tumors in woody hosts, but not in non-woody micropropagated plants. The use of transposon mutagenesis also uncovered a treasure trove of additional P. savastanoi genes affecting virulence and participating in diverse bacterial processes. Although there is still much to be learned on what makes a bacterium a successful pathogen of trees, we are already untying the knots.